Ten Tools for Managing Change in National Agricultural Research Organizations - Hobbs, S. Huntington (International Service for National Agricultural Research, 1999)
As the role of the public sector is being reconsidered in many industrialized and developing countries, national agricultural research organizations (NAROs) know that they must retool, or see their roles taken over by private institutions with fundamental motives other than increasing public well-being. But the process of change presents difficult problems for many developing-country NAROs. This research management guideline presents a five-phase program to help NARO leaders manage the change process in their institutions. The phases are (1) recognizing the need for change (2) creating pressure for change (3) deciding what to change (4) creating the conditions for implementation (5) achieving change. Each phase is supported by two tools, which are described in detail. The tools are a combination of proven methods from the management sciences and approaches developed or adapted by ISNAR. The book is the result of careful examination of numerous experiences in bringing about change, an extensive literature review, as well as numerous discussions with agricultural research managers in developing countries.